2013
DOI: 10.1002/imhj.21401
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Security in Three‐Year‐Olds who Entered Substitute Care in Infancy

Abstract: This study assessed relations among number of out-of-home placement changes, time in caregivers’ care, caregiver type (i.e., foster parent, adoptive parent, kinship relation, and biological parent), child gender, and caregiver-child Emotional Availability (EA) as predictive of child attachment security when children were 3 years old in a sample of 104 caregivers and children. Children entered court-ordered care by six months of age. On average, children at the age of three spent 30 months with their caregivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 91 publications
3
25
1
Order By: Relevance
“…Although EA sensitivity was highly and positively correlated with the other EA dimensions, consistent with findings obtained in other cultural contexts (Altenhofen, Clyman, Little, Baker, & Biringen, ; Bornstein et al., ; Kubicek, Riley, Coleman, Miller, & Linder, ), the criterion validity of the EA sensitivity scale was not met, as implied from the negative association between EA sensitivity and peer likability. The association between sensitivity and vocabulary did not reach statistical significance, but it was observed to be in the negative direction, which is inconsistent with theory.…”
Section: Discussionsupporting
confidence: 82%
“…Although EA sensitivity was highly and positively correlated with the other EA dimensions, consistent with findings obtained in other cultural contexts (Altenhofen, Clyman, Little, Baker, & Biringen, ; Bornstein et al., ; Kubicek, Riley, Coleman, Miller, & Linder, ), the criterion validity of the EA sensitivity scale was not met, as implied from the negative association between EA sensitivity and peer likability. The association between sensitivity and vocabulary did not reach statistical significance, but it was observed to be in the negative direction, which is inconsistent with theory.…”
Section: Discussionsupporting
confidence: 82%
“…Research has shown associations between bonding measured at different time-points in the perinatal period: Prenatal bonding has been associated with postnatal bonding (Rossen et al, 2016(Rossen et al, , 2017 while bonding was shown to be associated at 4 weeks, 4 months, and 8 months postnatal (Condon & Corkindale, 1998). While EA has been studied extensively in relation to attachment (Altenhofen, Clyman, Little, Baker, & Biringen, 2013;Altenhofen, Sutherland, & Biringen, 2010), including the Strange Situation protocol (Aviezer, Sagi, Joels, & Ziv, 1999;Aviezer, Sagi-Schwartz, & Koren-Karie, 2003;Biringen et al, 2005;Carter, Garrity-Rokous, Chazan-Cohen, Little, & Briggs-Gowan, 2001;Easterbrooks et al, 2000;Ziv, Aviezer, Gini, Sagi, & Koren-Karie, 2000), the relationship of early self-reported bonding (8 weeks postnatal) and EA at 12-months has yet to be examined. In particular, these associations have not previously been investigated in a large community sample that included both mothers and partners, using a longitudinal cohort study design.…”
Section: Subjective Appraisals Of the Parent-infant Bondmentioning
confidence: 99%
“…Some recent studies have observed emotional availability in adoptive parent-child dyads (Garvin et al 2012) or have specifically focused on the relation between attachment and emotional availability in adoptive and foster families (Altenhofen et al 2013;Van den Dries et al 2012 ). As a whole, they showed a good level of emotional availability in adoptive/foster families and provided some data in support of an association between child attachment and emotional availability.…”
Section: Introductionmentioning
confidence: 96%